Utilización de bloques nutricionales con cuatro niveles de inclusión (7, 9, 11, 15 %) de harina de hoja de Nopal (opuntia sp.) en la alimentación de cuyes de engorde. - Caiza Llumitasig, Edwin Efrain (2020)
The raising of fattening guinea pigs in the central region of Ecuador is very widespread, however there is not extensive knowledge about the most appropriate diets that can be supplied to the animals, so that they reach their maximum possible development. In this sense, the present research aims to carry out an experiment in which nutritional blocks are used with four inclusion levels of Nopal leaf flour (Opuntia Sp.), Namely the treatments are T0: (base diet), T1: (base diet + 7% Nopal flour addition), T2: (base diet + 9% Nopal flour addition) T3: (base diet + 11% Nopal flour addition) and T4: (base diet + 15% Nopal flour addition). For this purpose, a sample of 40 guinea pigs, 28 days old, were given the diet based on the indicated treatments for 8 weeks, taking 8 guinea pigs per treatment. The weights achieved by the guinea pigs at the end of the experiment were significantly higher than those of the control group, in males T4 was the most effective and in females it was T3. Regarding weight gain, the best result was presented by the T4 treatment in the case of male guinea pigs with a mean of 845.88 g, while in the case of T1 and T3 females they were equally effective. The dietary consumption of male guinea pigs of T4 was the one with the highest consumption, and of the females it was of T3. Regarding the food conversion, all the treatments that incorporate the nutritional blocks with Nopal leaf flour were significantly better than the control and similar between them, the best result was presented by T1 with a mean of 3.10. The yield to the carcass of the six guinea pigs slaughtered was comprised in the range of 50.93 and 59.20%, being that the control was the one that achieved the best performance to the carcass. Regarding the benefit/cost ratio of the implementation of the treatments with a base diet plus the nutritional blocks of Nopal leaf flour, it is established that the treatments T2 and T4 had the greatest utility.